IMPLEMENTASI PROGRAM KARTU INDONESIA PINTAR DI SDN INPRES TANJUNG RIA KOTA JAYAPURA - Evin Sibulun; Nur Aedah (JURNAL KEBIJAKAN PUBLIK, 2020)
The Smart Indonesia Program through the Smart Indonesia Card Program is a priority program of the President of the Republic of Indonesia, Ir. Joko Widodo is specifically designed to help children from poor or disadvantaged families to continue to get education services until they have finished secondary education or equivalent. The purpose of this study is to be able to analyze the implementation of the KIP program and identify things / factors that influence the implementation of the program, seen from George Edwards III aspects of communication, resources, disposition, and bureaucratic structure. This research uses a qualitative descriptive approach with data collection techniques through in-depth interviews (in-depth interviews), observation, and documentation studies. The results of the study showed that the implementation of KIP in Tanjung Ria SDN Inpres Kota Jayapura seen from the aspect of communication had not been effective. This can be seen from the lack of level of understanding of information from the recipient to the executor which contains clarity, among others: The absence of a Technical Guide, and the absence of Standard Operating Procedures for the implementation of the policy in the school. Viewed from the aspect of resources (human and financial), it is not effective. This can be seen from the lack of professional management human resources, and the process of channeling funds that are not yet on target. Viewed from the aspect of disposition (attitude of the implementer) shows the executor's responsibility to the recipient. This can be seen from the fact that the recipient is not yet satisfied. And from the aspect of bureaucratic structure the results showed that the management team that had been formed had not run well within the Tanjung Ria SDN Inpres Jayapura City. Supporting factors: communication, support, equipment resources, and information. The inhibiting factors: communication, capital resources and data accuracy